In-silico trials of targeted screening for abdominal aortic aneurysms using linked healthcare data: A study protocol - Liam Musto; Athanasios Saratzis; Mintu Nath; Emmanuel Katsogridakis; Ann Elsworth; Sylwia Bujkiewicz; Clark Hobson; Claire Lawson; Susan Wallace; Maria Gonzalez-Aguado; Aiden Smith; Susan Hodgson; et al. (PLoS ONE, 2025)
Background The NHS abdominal aortic aneurysm (AAA) screening programme (NAAASP) is both clinically and economically effective. One of the main determinants of this effectiveness is disease prevalence. AAA prevalence is decreasing over time, steadily reducing the efficiency of the current NAAASP screening policy. One alternative to whole population screening is targeted screening of high-risk groups. Whether this would detect a clinically and publicly acceptable proportion of disease, and whether it would improve cost-effectiveness are unknown. The aim of this research is to estimate the clinical outcomes and cost-effectiveness of targeted AAA screening. Methods Rather than conducting an expensive and time-consuming randomized trial to directly test targeted screening, we will undertake in-silico trials of targeted AAA screening. To determine success criteria for in-silico trials, the ethics and issues around the acceptability of targeted screening will first be explored through focus groups and interviews. A qualitative evidence synthesis to identify issues associated with targeted screening will be used to establish themes and topic guides. To perform the in-silico trials, individual men’s outcomes from the NAAASP (2013–2024, ≈ 2,500,000 men, ≈ 1% with AAA) will be linked to primary care data from the Clinical Practice Research Datalink (CPRD) (20% overlap of records). Risk factors for AAA will be identified by developing a risk prediction model and used as targeted screening criteria in in-silico trials, with diagnostic accuracy as the primary outcome. A discrete event simulation model will be adopted to extrapolate the trial findings beyond the observed period. We will estimate the clinical and cost-effectiveness of targeted screening compared with the current whole population screening strategy. Data linkage will be undertaken under Health Research Authority Confidentiality Advisory Group (Section 251) approval. Linked data will be effectively anonymised. Participants in the qualitative substudy will provide informed consent for participation. Discussion We expect this project to have a direct and significant impact on NHS, UK and worldwide AAA screening policies. The study findings will be submitted for publication in peer-reviewed journals and presented at scientific meetings.